PENDAMPINGAN BELAJAR SISWA MELALUI MEDIA GAMBAR GUNA MENINGKATKAN MINAT BELAJAR SISWA DI ERA COVID-19 - Imam Mashuri; Zulvi Afif Tianda (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
Student learning assistance aims to increase students' learning interest, this devotion program is carried out by applying several methods including: the preparatory stage consisting of interviews to parents of students, the delivery of activity schedules, and the preparation of materials, the implementation stage consisting of the implementation of activities initiated by approaching and mentoring students, post test evaluation stage in the form of images described and commented on. The results of activities that have been achieved are the assistance of students' learning in the covid-19 era by utilizing used goods as face shields with the provision of images for reference, student learning assistance in utilizing cartoon image media in the form of limbs and objects in the surrounding environment, student learning assistance in utilizing poster image media in the form of wudhu and pray.